2019
DOI: 10.1016/j.avsg.2018.07.043
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Concentration of Cathepsin A, D, and E and the Concentration of Copper and Zinc, and the Size of the Aneurysmal Enlargement in the Wall of the Abdominal Aortic Aneurysm

Abstract: Background: Despite advances in diagnostics and treatment, aortic aneurysms are an important clinical problem, mainly due to the accompanying complications that may lead to direct loss of life, also the number of diagnosed and operated aneurysms is constantly increasing. The aim of this study is to determine the relationship between the concentration of lysosomal peptidases cathepsin A, D, and E in the wall of the abdominal aortic aneurysm and the concentration of copper and zinc, and the size of the aneurysm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Aortic aneurysm involves dramatic changes in the structural components of the vasculature, due to SMC dysfunction, imbalance between proteinases and their inhibitors, and abnormal synthesis, accumulation, or degradation of ECM proteins 3 . Among different classes of proteases, metalloproteinases (MMPs, ADAMs, and ADAM-TSs) 83,88,98,99 , and cathepsins 100,101 are important factors for pathogenesis of aneurysm, because of their involvement in cleavage of different ECM and non-ECM proteins. The availability of genetically modified mouse models has paved the way to understanding the role of the ECM and its remodeling, the importance of protease and their inhibitors, and the contribution of different proteoglycans and glycoproteins in aortic aneurysm.…”
Section: Ecm-regulatory Proteins In Aortic Aneurysmmentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic aneurysm involves dramatic changes in the structural components of the vasculature, due to SMC dysfunction, imbalance between proteinases and their inhibitors, and abnormal synthesis, accumulation, or degradation of ECM proteins 3 . Among different classes of proteases, metalloproteinases (MMPs, ADAMs, and ADAM-TSs) 83,88,98,99 , and cathepsins 100,101 are important factors for pathogenesis of aneurysm, because of their involvement in cleavage of different ECM and non-ECM proteins. The availability of genetically modified mouse models has paved the way to understanding the role of the ECM and its remodeling, the importance of protease and their inhibitors, and the contribution of different proteoglycans and glycoproteins in aortic aneurysm.…”
Section: Ecm-regulatory Proteins In Aortic Aneurysmmentioning
confidence: 99%
“…Cathepsins are a group of serine, aspartic, and cysteine proteases, which contribute to vascular remodelling. Several cathepsins, including cathepsins A, D, S, K, and L are reported to be involved or upregulated in humans aortic aneurysmal tissues 100,101,118 . Cathepsin K and S are potent elastases that are produced by SMCs and macrophages in the aorta under inflammatory milieus.…”
Section: Cathepsinsmentioning
confidence: 99%
“…Cathepsins are a family of cysteine proteases that have been suggested to contribute to aneurysm onset and progression. Cathepsins A, D, K, L, and S are elevated in human AAA samples (62,118,244). Cathepsin K and S can be produced by SMCs and macrophages under inflammatory conditions and have strong elastinolytic activities (83,195,207).…”
Section: Cathepsinsmentioning
confidence: 99%
“…Demir, et al [22] found that vitamin D de ciency was an independent factor for aortic dilatation. Adam and his team discovered the concentration of Copper and Zinc was signi cant associated with the size of the aneurysmal enlargement in the wall of the abdominal aortic aneurysm [23]. In addition, although there was no research has speci cally evaluated the relationship between Chinese early life famine exposure and AAD in adulthood, we further found that there was a stronger risk of AAD in female, BMI ≥ 24 kg/m 2 , smokers, hypertensive patients, and this effect has not been adjusted by the above traditional risk factors for AAD.…”
Section: Discussionmentioning
confidence: 99%